Supporting people with type 2 diabetes in effective use of their medicine through mobile health technology integrated with clinical care (SuMMiT-D pilot): results of a feasibility randomised trial - Farmer, AJ; Allen, J; Bartlett, YK; Bower, P; Chi, Y; French, DP; Gudgin, B; Holmes, E; Horne, R; Hughes, DA; Jones, L; Kenning, C; et al. (BioMed Central, 2024)
Background The purpose of this 6-month intervention pilot feasibility randomised trial was to test sending brief messages using mobile phones to promote self-management through taking medication as prescribed to people with type 2 diabetes. This was to inform the design and conduct of a future large-scale United Kingdom-based clinical trial and establish the feasibility of recruitment, the technology used, follow-up, and data collection.